1992
DOI: 10.1063/1.108483
|View full text |Cite
|
Sign up to set email alerts
|

YBa2Cu3O7−y microbridges on Y2O3/yttria-stabilized zirconia/SiO2/Si(100)

Abstract: YBa2Cu3O7−y (YBCO) microbridges have been fabricated on a SiO2/Si substrate using Y2O3/YSZ (yttria-stabilized zirconia) buffer layer. Using polycrystalline silicon layer overlaid on oxidized Si(100) single crystal, the bridge is microprocessed by means of electron beam lithography and dry etching. The fabricated configuration serves as a mask for depositing YSZ and Y2O3 double buffer layers. The YBCO layer is deposited on the substrate by means of laser ablation deposition. The dimension of the bridge is 1.7 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Up to now, the growth of GaN crystals has been extensively investigated by several research groups using different preparation approaches mainly including flux growth [5,6], hydride vapor-phase epitaxy [7,8], pressure-controlled solution growth [9], high-pressure ammonothermal growth [10], mechanochemical reaction method [11] and so on. Because of the importance of application of GaN on optoelectronic industry, the pursuit of the optimal synthetic route to attain well-crystallized GaN crystals has not stopped so far.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the growth of GaN crystals has been extensively investigated by several research groups using different preparation approaches mainly including flux growth [5,6], hydride vapor-phase epitaxy [7,8], pressure-controlled solution growth [9], high-pressure ammonothermal growth [10], mechanochemical reaction method [11] and so on. Because of the importance of application of GaN on optoelectronic industry, the pursuit of the optimal synthetic route to attain well-crystallized GaN crystals has not stopped so far.…”
Section: Introductionmentioning
confidence: 99%
“…Using a PrBa 2 Cu 3 O 7−δ (PBCO) template layer, Inam et al observed a high T c onset of 92 K and smooth surfaces. Subsequently, using this technique a-axis-oriented films have been successfully grown on a variety of different substrates, including MgO and LAO, with the transition temperature between 82 and 89 K. In particular, highly epitaxial films with high T c and large anisotropy have been reported on LaSrGaO 4 (LSGO) substrates [9,10]. In some reports, YBCO deposited at a low temperature was used as the template layer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrications of various types [1][2][3][4][5] of high-T c Josephson junctions has been of current interest because of the potential applications of Josephson junctions in superconducting instruments. In this work we fabricate U-shape microbridges of 20 p.m wide, 10 gm long and 10 -40 nm thick by photolithography and wet etching and report the current-voltage (I-V) characteristics and microwave effects of the bridges.…”
mentioning
confidence: 99%